Organization of blood donor panels after the war (1944)
1944 1944 1940s 2 pages ORGANIZATION OF BLOOD DONOR PANELS AFTER THE WAR. A conference was held at the Ministry of Health on the 28th March, 1944, under the chairmanship of Sir Francis Fraser, Director-General Emergency Medical Services. There were present representatives of the Ministry of Health, Medical Research Council, the Service Departments, Ministry of Labour and National Service, Department of Health for Scotland, Ministry of Home Affairs Northern Ireland; representatives of the headquarters of the British Red Cross Society, Order of St. John of Jerusalem, Women's Voluntary Services, Voluntary Blood Donors Association, Trades Union Congress, Boy Scouts Association (Rover Scouts), and Toc H; and representatives of other major donor panels co-operating with the Emergency Blood Transfusion Service. The conference first considered the proposal that a central committee should be formed to co-ordinate the post-war work of the various bodies concerned in the organization of donor panels throughout the country and in the protection of the welfare and interests of donors. The chairman explained that the organization of the post-war hospital service, as proposed in the White Paper recently issued, would be the responsibility of the new joint hospital authorities in each suitably sized local area. It would be for these authorities to consider how to recruit blood donors; but the Ministry considered that as a rule they would be glad of the assistance of voluntary effort in organizing donor panels and the welfare of donors. The scope of a central committee would be to advise on such matters as the general conditions of a donor service, the effect on the welfare of donors of the development of the technical and medical aspects of blood transfusion, recruitment, publicity and conditions of insurance; to disseminate information collected from all areas of the country and also from countries abroad; and to act as intermediary between donors and employers. Some form of central co-ordinating committee would be of particular value during the interim period after the Emergency Medical Service had been demobilized and before -1- 292/845.2/4/34